The Multilingual Students' Voyage Towards International Scale Settings: Challenges And Expectations. - Nesba, Asma . (University of Eloued جامعة الوادي, 2021)
The current study aims at tracking the social and academic linguistic performance of international students from three African countries studying in the Algerian universities. The early stage of involvement in a new different multilingual context can affect significantly the academic practices of international students. To get in-depth insights into this area of research a qualitative study during the academic year 2020/2021 was conducted at the universities of El-Oued and Annaba. Two data gathering tools were utilized, a questionnaire as well as a structured interview. The findings reveal that the students’ prior experiences as being members in small-scale multilingualism settings enabled them to adhere quickly to a larger multilingual scale. A cultural openness was also noticed among the host society when peer colleagues’ curiosity to know about the other different led them to be in close contact with international students